1971
DOI: 10.1042/bj1230261
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of sodium oestrone [35S]sulphate in the rat

Abstract: Intraperitoneal, intravenous or oral administration of sodium oestrone [(35)S]-sulphate to male and female Medical Research Council hooded rats is followed by the rapid excretion of the bulk of the radioactivity in urine in the form of inorganic [(35)S]sulphate. Pre-treatment of rats with an antibiotic regimen does not affect the results except in the case of oral administration, when relatively large amounts of the dose are recovered as ester [(35)S]sulphate in faeces. Intravenous administration of the labell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

1972
1972
1993
1993

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…radioactivity approx. 6mCi/mmol) as described by Dolly et al (1971). The potassium salts of p-acetylphenyl sulphate and p-nitrophenyl sulphate were synthesized by the method of Burkhardt & Lapworth (1926) as modified by Milsom et al (1972).…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…radioactivity approx. 6mCi/mmol) as described by Dolly et al (1971). The potassium salts of p-acetylphenyl sulphate and p-nitrophenyl sulphate were synthesized by the method of Burkhardt & Lapworth (1926) as modified by Milsom et al (1972).…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…However, it is noteworthy that Hanahan & Everett (1950) have shown that injected sodium oestrone [35S]sulphate undergoes appreciable desulphation in the rat with the rapid excretion of inorganic [35S]sulphate in the urine. Moreover, the liver was found to be the principal organ of the rat where the desulphation of injected oestrone [35S]_ sulphate occurs (Dolly et al, 1971). Several investi-gators have reported that rat and human tissues have the capacity to desulphate oestrone sulphate (see Pulkkinen, 1961;Notation & Ungar, 1969;Pack & Brooks, 1970;Schwers & Rodesch, 1963;Sandberg & Jenkins, 1966), the responsible enzyme being localized in the microsomal fraction of the cell (Pulkkinen & Paunio, 1963;Zuckerman &Hagerman, 1969;French & Warren, 1966).…”
mentioning
confidence: 99%
“…After incubation of oestradiol with rat liver preparations hy¬ droxylation has also been shown to occur at C-2, C-6 and C-l6 (Hagopian 8c Levy 1958;Breuer 8c Knuppen 1960;Favu et al 1969;Brooks 8c Horn 1971;Worlmann et al 1972). Oestrone sulphate administered intraperitoneally or intravenously is rapidly hydrolysed and the sulphate radical is rapidly excreted in the urine (Dolly et al 1971). In animals with the bile duct catherized, only small amounts of radioactivity were detected in bile and this was mainly in the form of oestrone and oestradiol sulphates.…”
Section: G Metabolism Of Oestrogens In Ratsmentioning
confidence: 99%
“…The relative amount of radioactivity associated with each area was measured from the record of the scanner as described by Dodgson and Tudball (12). Total radioactivity in liquid samples was also determined by scintillation counting by the method of Dolly et al (13).…”
mentioning
confidence: 99%